Endocan: A Novel Marker for Colchicine Resistance in Familial Mediterranean Fever Patients? - Omma, Ahmet; Armaǧan, Berkan; Güven, Serdar Can; Sandıkçı, Sevinç Can; Çolak, Seda; Yücel, Çiǧdem; Küçükşahin, Orhan; Erden, Abdulsamet (Frontiers in Pediatrics, 2021)
Introduction: Familial Mediterranean fever (FMF) patients had 5–10% colchicine resistance. Although FMF attacks are characterized by acute phase elevation, there are no biomarkers that can show colchicine resistance yet. The serum endocan levels may elevate in inflammatory and auto-inflammatory diseases. Objectives: This study aimed to evaluate serum endocan levels in FMF patients according to whether attack and colchicine resistance or not and also compare them with classical acute phase reactants. Methods: In this single-center and cross-sectional study, a total of 111 FMF patients and 60 healthy individuals were enrolled. All patients' basic demographic and clinical data were recorded and blood samples were collected. Results: A total of 46 (41.4%) FMF patients had colchicine resistance. In comparison to the FMF patients according to colchicine response, colchicine resistance patients had a significantly higher median (IQR) endocan levels than colchicine responsive patients [36.98 ng/ml (97.41) vs. 13.57 ng/ml (27.87), p = 0.007], but there were no differences between in terms of median ESR and CRP levels. Inversely, serum endocan levels were similar during an attack and attack-free period in FMF patients, although ESR and CRP levels were significantly different. Interestingly, the highest serum endocan levels were in the control group. Conclusion: In conclusion, serum endocan levels were higher in colchicine resistance than colchicine responsive patients, but attack state had no effect on serum endocan levels in our study. Unlike ESR and CRP, serum endocan may be a novel biomarker for detection of colchicine resistance and distinguish the FMF attacks.